Embracing the Future: Digital School Culture in Tabanan High Schools - Reynald Setyawan (Kata Kita: Journal of Language, Literature, and Teaching, 2022)
Digitalization has been an inevitable part of human lives, and education is not an exception. Digitalization is, however, only a part of the change. While digitalization is just using digital technologies and digitized data for an impact, digital transformation is broader adoption of digital technology and cultural change. It is more about the people, rather than the technology. One of the most prominent examples is the integration of the digital culture and the school culture, creating “digital school culture”. Concerns arise from the change, especially isolation from peers and decreased effectiveness on practical lessons . In this case, the creativity to integrate digital culture in online settings to accommodate these concerns is necessary. This research attempts to find the three high schools in Tabanan’s current state of digital school culture and plan of development for the future. The data is gained through semi-impromptu interviews with three high schools’ vice-principal of curriculum and vice-principal of student affairs in Tabanan. Their answers are then analyzed through digital culture and school culture theory. Their answers will also be compared with each other to figure out the similarities and differences in their implementation of digital school culture.Keywords: digital culture, school culture, digital school culture, digital transformation, digital native, digital immigrant, Tabanan high school